The Impact of Technological-Organizational-Environmental Factors on Electronic Marketing Performance of Food and Beverage SMES in Kuwait - Alkhanaini, Mohammad A. S.; Mohaidin, Zurina; Othman , Rosly (International Review of Management and Marketing, 2025)
This study aims to examine the relationship between the Technology-Organization-Environment (TOE) framework and electronic marketing performance among small and medium enterprises (SMEs) in Kuwait’s restaurant and food and beverage sector. While digital platforms and technologies are increasingly essential for improving business operations, the strategic alignment between TOE factors and marketing outcomes remains unclear. Therefore, determining this relationship forms the core problem addressed in this research. A quantitative research method was employed using a self-administered questionnaire to collect data from SME stakeholders. The findings indicate that certain TOE dimensions such as compatibility and organizational readiness significantly impact profitability, while top management support and mobile payment gateway usage are positively associated with sales growth. The study highlights the importance of leveraging TOE elements to enhance marketing performance and recommends stronger organizational readiness, managerial involvement, and digital platform integration to drive marketing success within SMEs.